Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Get detailed and precise answers to your questions from a dedicated community of experts on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Sure, let's solve the system of equations by graphing them step-by-step:
The system of equations is:
1. [tex]\(-3x - y = -10\)[/tex]
2. [tex]\(4x - 4y = 8\)[/tex]
### Step 1: Rewrite each equation in slope-intercept form [tex]\(y = mx + b\)[/tex].
#### Equation 1: [tex]\(-3x - y = -10\)[/tex]
Solve for [tex]\(y\)[/tex]:
[tex]\[ - y = 3x - 10 \][/tex]
[tex]\[ y = -3x + 10 \][/tex]
#### Equation 2: [tex]\(4x - 4y = 8\)[/tex]
First, let's divide every term by 4 to simplify it:
[tex]\[ x - y = 2 \][/tex]
Solve for [tex]\(y\)[/tex]:
[tex]\[ -y = -x + 2 \][/tex]
[tex]\[ y = x - 2 \][/tex]
### Step 2: Graph each of the equations on the same set of axes.
#### Graph of [tex]\(y = -3x + 10\)[/tex]:
1. Find the y-intercept [tex]\((0, b)\)[/tex]: When [tex]\(x = 0\)[/tex], [tex]\(y = 10\)[/tex]. So, one point is [tex]\((0, 10)\)[/tex].
2. Find another point using the slope [tex]\(-3\)[/tex]: The slope is [tex]\(-3\)[/tex], meaning the rise is -3 and the run is 1. From [tex]\((0, 10)\)[/tex], move down 3 units and to the right 1 unit. This gives the point [tex]\((1, 7)\)[/tex].
#### Graph of [tex]\(y = x - 2\)[/tex]:
1. Find the y-intercept [tex]\((0, b)\)[/tex]: When [tex]\(x = 0\)[/tex], [tex]\(y = -2\)[/tex]. So, one point is [tex]\((0, -2)\)[/tex].
2. Find another point using the slope [tex]\(1\)[/tex]: The slope is [tex]\(1\)[/tex], meaning the rise is 1 and the run is 1. From [tex]\((0, -2)\)[/tex], move up 1 unit and to the right 1 unit. This gives the point [tex]\((1, -1)\)[/tex].
### Step 3: Determine the point of intersection.
When you graph both lines, you will observe that they intersect at the point where both equations satisfy the same pair of [tex]\( (x, y) \)[/tex] values.
### Step 4: Check the solution with the given values.
Since we are using the intersection point from the graph:
[tex]\[ (x, y) = (3, 1) \][/tex]
### Step 5: Verify the Point of Intersection
To verify whether [tex]\( (3, 1) \)[/tex] is the solution, we substitute these values back into the original equations:
For [tex]\( -3x - y = -10 \)[/tex]:
[tex]\[ -3(3) - 1 = -9 - 1 = -10 \quad \text{(True)} \][/tex]
For [tex]\( 4x - 4y = 8 \)[/tex]:
[tex]\[ 4(3) - 4(1) = 12 - 4 = 8 \quad \text{(True)} \][/tex]
Thus, the solution to the system of equations is indeed [tex]\( (3, 1) \)[/tex].
As a result, the point of intersection and the solution to the system is:
[tex]\[ \boxed{(3, 1)} \][/tex]
The system of equations is:
1. [tex]\(-3x - y = -10\)[/tex]
2. [tex]\(4x - 4y = 8\)[/tex]
### Step 1: Rewrite each equation in slope-intercept form [tex]\(y = mx + b\)[/tex].
#### Equation 1: [tex]\(-3x - y = -10\)[/tex]
Solve for [tex]\(y\)[/tex]:
[tex]\[ - y = 3x - 10 \][/tex]
[tex]\[ y = -3x + 10 \][/tex]
#### Equation 2: [tex]\(4x - 4y = 8\)[/tex]
First, let's divide every term by 4 to simplify it:
[tex]\[ x - y = 2 \][/tex]
Solve for [tex]\(y\)[/tex]:
[tex]\[ -y = -x + 2 \][/tex]
[tex]\[ y = x - 2 \][/tex]
### Step 2: Graph each of the equations on the same set of axes.
#### Graph of [tex]\(y = -3x + 10\)[/tex]:
1. Find the y-intercept [tex]\((0, b)\)[/tex]: When [tex]\(x = 0\)[/tex], [tex]\(y = 10\)[/tex]. So, one point is [tex]\((0, 10)\)[/tex].
2. Find another point using the slope [tex]\(-3\)[/tex]: The slope is [tex]\(-3\)[/tex], meaning the rise is -3 and the run is 1. From [tex]\((0, 10)\)[/tex], move down 3 units and to the right 1 unit. This gives the point [tex]\((1, 7)\)[/tex].
#### Graph of [tex]\(y = x - 2\)[/tex]:
1. Find the y-intercept [tex]\((0, b)\)[/tex]: When [tex]\(x = 0\)[/tex], [tex]\(y = -2\)[/tex]. So, one point is [tex]\((0, -2)\)[/tex].
2. Find another point using the slope [tex]\(1\)[/tex]: The slope is [tex]\(1\)[/tex], meaning the rise is 1 and the run is 1. From [tex]\((0, -2)\)[/tex], move up 1 unit and to the right 1 unit. This gives the point [tex]\((1, -1)\)[/tex].
### Step 3: Determine the point of intersection.
When you graph both lines, you will observe that they intersect at the point where both equations satisfy the same pair of [tex]\( (x, y) \)[/tex] values.
### Step 4: Check the solution with the given values.
Since we are using the intersection point from the graph:
[tex]\[ (x, y) = (3, 1) \][/tex]
### Step 5: Verify the Point of Intersection
To verify whether [tex]\( (3, 1) \)[/tex] is the solution, we substitute these values back into the original equations:
For [tex]\( -3x - y = -10 \)[/tex]:
[tex]\[ -3(3) - 1 = -9 - 1 = -10 \quad \text{(True)} \][/tex]
For [tex]\( 4x - 4y = 8 \)[/tex]:
[tex]\[ 4(3) - 4(1) = 12 - 4 = 8 \quad \text{(True)} \][/tex]
Thus, the solution to the system of equations is indeed [tex]\( (3, 1) \)[/tex].
As a result, the point of intersection and the solution to the system is:
[tex]\[ \boxed{(3, 1)} \][/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.